Innate Immune Responses of Vaccinees Determine Early Neutralizing Antibody Production After ChAdOx1nCoV-19 Vaccination - Shen, Ching-Fen; Yen, Chia-Liang; Fu, Yi-Chen; Cheng, Chao-Min; Shen, Tzu-Chi; Chang, Pei-De; Cheng, Kuang-Hsiung; Liu, Ching-Chuan; Chang, Yu-Tzu; Chen, Po-Lin; Ko, Wen-Chien; Shieh, Chi-Chang (Frontiers in Immunology, 2022)
Background Innate immunity, armed with pattern recognition receptors including Toll-like receptors (TLR), is critical for immune cell activation and the connection to anti-microbial adaptive immunity. However, information regarding the impact of age on the innate immunity in response to SARS-CoV2 adenovirus vector vaccines and its association with specific immune responses remains scarce. Methods Fifteen subjects between 25-35 years (the young group) and five subjects between 60-70 years (the older adult group) were enrolled before ChAdOx1 nCoV-19 (AZD1222) vaccination. We determined activation markers and cytokine production of monocyte, natural killer (NK) cells and B cells ex vivo stimulated with TLR agonist (poly (I:C) for TLR3; LPS for TLR4; imiquimod for TLR7; CpG for TLR9) before vaccination and 3-5 days after each jab with flow cytometry. Anti-SARS-CoV2 neutralization antibody titers (surrogate virus neutralization tests, sVNTs) were measured using serum collected 2 months after the first jab and one month after full vaccination. Results The older adult vaccinees had weaker vaccine-induced sVNTs than young vaccinees after 1st jab (47.2±19.3% vs. 21.2±22.2%, p value<0.05), but this difference became insignificant after the 2nd jab. Imiquimod, LPS and CpG strongly induced CD86 expression in IgD+CD27- naïve and IgD-CD27+ memory B cells in the young group. In contrast, only the IgD+ CD27- naïve B cells responded to these TLR agonists in the older adult group. Imiquimode strongly induced the CD86 expression in CD14+ monocytes in the young group but not in the older adult group. After vaccination, the young group had significantly higher IFN-γ expression in CD3- CD56dim NK cells after the 1st jab, whilst the older adult group had significantly higher IFN-γ and granzyme B expression in CD56bright NK cells after the 2nd jab (all p value <0.05). The IFN-γ expression in CD56dim and CD56bright NK cells after the first vaccination and CD86 expression in CD14+ monocyte and IgD-CD27-double-negative B cells after LPS and imiquimod stimulation correlated with vaccine-induced antibody responses. Conclusions The innate immune responses after the first vaccination correlated with the neutralizing antibody production. Older people may have defective innate immune responses by TLR stimulation and weak or delayed innate immune activation profile after vaccination compared with young people.